2015
DOI: 10.4103/0300-1652.171622
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and outcome of fetal macrosomia in a Nigerian tertiary hospital

Abstract: Background:To determine the incidence and risk factors of fetal macrosomia and maternal and perinatal outcome.Patients and Methods:This was a 1-year prospective case–control study of singleton pregnancies in a Nigerian tertiary hospital. Only women who gave consent were recruited for the study. The maternal and perinatal outcomes in women who delivered macrosomic infants (birth weight ≥ 4000 g) were compared with the next consecutive delivery of normal birth weight (2500–3999 g) infants.Results:The total deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
4
14
2
Order By: Relevance
“…This was within the range of 3%-15% reported by Muhamadbeigi et al, (2011) [20]. It was also consistent with rates reported by other studies in southern Nigeria but it was higher than the rate reported in similar study in the University of Benin Teaching, Benin City where Olokor et al, (2015) [19] found a prevalence rate of 5.4%. This intra-city variation in prevalence rate may be due to the higher clientele in St. Philomena's Hospital due to easier accessibility and affordability.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This was within the range of 3%-15% reported by Muhamadbeigi et al, (2011) [20]. It was also consistent with rates reported by other studies in southern Nigeria but it was higher than the rate reported in similar study in the University of Benin Teaching, Benin City where Olokor et al, (2015) [19] found a prevalence rate of 5.4%. This intra-city variation in prevalence rate may be due to the higher clientele in St. Philomena's Hospital due to easier accessibility and affordability.…”
Section: Discussionsupporting
confidence: 71%
“…In Nigeria, prevalence of fetal macrosomia seems to vary according to the geographical regions. While it is higher in the rain forest regions in the southern parts of Nigeria, [19,21,22] it is relatively less in the savannah regions of Northern regions [23]. The variations in prevalence according to geographical region may be suggestive of dietary factors and cultural habits as predisposing factors of fetal macrosomia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have indeed shown a relation between dystocia and increasing macrosomic weight [25], interventional deliveries, shoulder dystocia, and genital laceration [26], but we found no relation between fetal weight and mode of delivery (p=0,156, Table 5). Bekdas et al analyzing 509 macrosomic newborns from non-diabetic mothers with 500 healthy ones, also found no difference in the mode of delivery, [4], revealing the probability of the implication of other fetal anthropometric factors.…”
Section: Route Of Deliverycontrasting
confidence: 75%